Rancang Bangun Generator Magnet Permanen Fluksi Aksial Single Stator Single Rotor - Yuhendri, Muldi; Doni, Dona; Ikhfa, Anne Fadia (Fakultas Teknik Universitas Muria Kudus, 2023)
Permanent magnet synchronous generator is one type of generator that is widely used for small-scale power generation, because it can be operated at low speed, so it does not require a gearbox in its operation. This paper proposes the manufacture of a low speed axial flux permanent magnet synchronous generator that can be used for small-scale electric power generation. The generator is designed in the form of a single stator single rotor. The generator stator is designed using fiberglass as the holder for the nine coils, while the rotor is designed in a disc shape using aluminum as the holder for the Neodymium N52 permanent magnet. The generator design was validated through Finite Element Analysis simulation using solidwork and tested through experiments using an induction motor as the driving force. Tests were carried out with varying air gaps and rotational speeds. The experimental results show that the generator can produce a voltage of 15.4 Volts when the generator is rotated at a speed of 500 rpm. The generator can also produce a maximum power of 400 Watts with an air gap of 2 mm.